2017
DOI: 10.1101/192591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contribution of the β-glucosidase BglC to the Onset of the Pathogenic Lifestyle ofStreptomyces scabies

Abstract: 2Common scab disease on root and tuber plants is caused by Streptomyces scabies and related 2 3 species which use the cellulose synthase inhibitor thaxtomin A as main phytotoxin. 4Thaxtomin production is primarily triggered by the import of cello-oligosaccharides. Once 2 5 inside the cell, the fate of the cello-oligosaccharides is dichotomized into i) fueling glycolysis 2 6with glucose for the saprophytic lifestyle through the action of β -glucosidase(s) (BG), and ii) reduced production of thaxtomin when the m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Deletion of bglC strongly decreased the levels of thaxtomin production. 16 Earlier proteomics work assessed the global response of S. scabies grown under conditions eliciting pathogenesis, such as in the presence of suberin, or inhibiting pathogenesis, in the tatC mutant. [17][18][19][20] Two-dimensional (2D)-PAGE coupled with N-terminal sequencing or tandem mass spectrometry showed the overproduction of proteins linked to bacterial stress response, specific metabolic pathways, and proteins known to be involved in secondary metabolism and morphological differentiation due to the presence of suberin.…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of bglC strongly decreased the levels of thaxtomin production. 16 Earlier proteomics work assessed the global response of S. scabies grown under conditions eliciting pathogenesis, such as in the presence of suberin, or inhibiting pathogenesis, in the tatC mutant. [17][18][19][20] Two-dimensional (2D)-PAGE coupled with N-terminal sequencing or tandem mass spectrometry showed the overproduction of proteins linked to bacterial stress response, specific metabolic pathways, and proteins known to be involved in secondary metabolism and morphological differentiation due to the presence of suberin.…”
Section: Introductionmentioning
confidence: 99%
“…scabiei showed reduced tissue hypertrophy on potato tuber slices, but the impact of the mutant has only been assessed on tobacco in vivo and not on its natural hosts which questions the relevance of this molecule in the colonization process (43). Apart from the results on the mutants involved in the biosynthesis of thaxtomins (5,22,23,41), it is thus sometimes difficult to draw conclusions on the importance of a BGC in contributing to the capacity of S . scabiei to colonize and infect root and tuber plants.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the inactivation of scab_1471 in S. scabiei resulted in a mutant strain unable to produce pyochelin but showing no sign of reduced virulence, indicating that this siderophore is either not essential for pathogenicity, or that its absence is rescued by other siderophore(s) produced by S. scabiei (20). Also, the interference with thaxtomin production caused by the inactivation of the cellobiose and cellotriose beta-glucosidase BglC (41) revealed a genetic compensation phenomenon that awakened the expression of alternative beta-glucosidases allowing S . scabiei to maintain the capacity to use cello- oligosaccharides (42).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, a set of in vivo genome editing methods have been developed to facilitate pathway engineering and modification. However, previous studies for genome editing in Streptomyces were mainly based on the traditional double crossover or single crossover . Luckily, with the advent of CRISPR systems, tools for site‐specific genome editing in Streptomyces were rapidly developed (Figure ).…”
Section: Current Synthetic Biology Tools Developed For Applications Imentioning
confidence: 99%
“…Previous work demonstrated that cebR is the cellobiose‐sensing key, which locks the expression of txtR , while txtR is the key necessary to unlock the production of phytotoxin . With the understanding of the regulation relationship between the regulons cebR and txtR , the constitutive thaxtomin A production and hypervirulence of Streptomyces scabies were obtained by the cebR deletion . In addition, the increase of milbemycin production was attributed to the deletion of SbbA in the SbbR/SbbA pair (an important ArpA/AfsA ‐like system) in a BGC from Streptomyces bingchenggensis BC04 .…”
Section: Pathway‐specific Engineering To Exploit Natural Products Biomentioning
confidence: 99%